THE ROLE OF ARTIFICIAL INTELLIGENCE IN EDUCATION: METHODOLOGICAL FOUNDATIONS AND PEDAGOGICAL IMPLICATIONS - Khojaniyazova Bazargul Mambetovna (Modern American Journals, 2026)
The rapid development of artificial intelligence (AI) has significantly influenced modern educational systems, transforming traditional pedagogical approaches and instructional methodologies. This study investigates the methodological foundations of AI integration in education and examines its impact on learning outcomes, student engagement, and teaching efficiency. Using a mixed-method research design, the study analyzes quantitative performance data and qualitative feedback from students and instructors involved in AI-assisted instruction. The findings demonstrate that AI-based adaptive learning systems improve academic performance, increase learner motivation, and optimize instructional processes. However, ethical considerations and pedagogical balance remain critical factors for sustainable implementation. The study concludes that AI serves as a complementary pedagogical tool that enhances educational effectiveness when aligned with sound methodological principles.
Keywords: Artificial intelligence, educational technology, teaching methodology, adaptive learning, digital pedagogy, personalized instruction, learning outcomes.